2014
DOI: 10.1055/s-0034-1372483
|View full text |Cite
|
Sign up to set email alerts
|

An Autologously Generated Platelet-Rich Plasma Suturable Membrane May Enhance Peripheral Nerve Regeneration after Neurorraphy in an Acute Injury Model of Sciatic Nerve Neurotmesis

Abstract: Our data show that the application of a PRP fibrin membrane around the neurorraphy improves the nerve regeneration process in a rat sciatic nerve model. The use of PRP as a suturable membrane could perform an action not only as a source of bioactive proteins but also as a nerve guide to hold the scar reaction and thus improve axonal regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 25 publications
0
33
0
3
Order By: Relevance
“…Giannessi et al . 13 commented that PRP could be a nerve guide to diminish scar reaction during axonal regeneration in a rat sciatic nerve model. Another study revealed that PRP could limit nerve damage 12 weeks post-injection in a rabbit model of 10% dextrose-induced MN injury (carpal tunnel model) 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Giannessi et al . 13 commented that PRP could be a nerve guide to diminish scar reaction during axonal regeneration in a rat sciatic nerve model. Another study revealed that PRP could limit nerve damage 12 weeks post-injection in a rabbit model of 10% dextrose-induced MN injury (carpal tunnel model) 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Among all, the issue here is about the effect of PRP on neural tissue and the concern of its effectiveness in the management of peripheral neuropathies and the relief of NP. Studies arguing in favor of the use of PRP in neuropathies and/or NP, consider that PRP or stem cells can exert an anti-inflammatory effect through cytokine release, and consider the role of PRP or stem cells in nerve healing and regeneration, combating thus the pathological inflammation involved in neuropathic pain (53)(54)(55)(56)(57). This …”
Section: Current Schemes Treatments For Np and Our Cell-based Proposalmentioning
confidence: 99%
“…PRP products hold an important therapeutic potential as a neuroprotective, neurogenic and neuroinflammatory therapeutic modulator system [46][47][48][49][50] and as enhancer of sensory and motor functional nerve-muscle unit recovery [51][52][53]. They are applied either as a filler of nerve conduits or vein-muscle grafts across nerve gaps post-trauma by ultrasound-guided perineural and intraneural infiltrations or as scaffolds to bridge or wrap the injured nerve stumps [54][55][56].…”
Section: Prp In the Management Of Neuropathiesmentioning
confidence: 99%